Assessment of "social" and "economic" sustainability in peri-urban territories: A proposal of methodological framework and its application to Lisbon Metropolitan Area - Costa, P. (2021)
Carried out within the framework of the multidisciplinary research project PERIURBAN (Peri-urban areas faced with the challenges of sustainability: developing scenarios for Lisbon Metropolitan Area) this article aims to propose, discuss and implement criteria for assessing the sustainability of peri-metropolitan territories at the social and economic level, starting from its application to the specific case of 5 parishes in Lisbon Metropolitan area.